Prospecting of breeding adult Common terns in an unstable environment. Issue 5 (3rd September 2019) - Martinović, Miloš; Galov, Ana; Svetličić, Ida; Tome, Davorin; Jurinović, Luka; Ječmenica, Biljana; Basle, Tilen; Božič, Luka; Kralj, Jelena
Abstract : With increasing advances in telemetry technology, prospecting behaviour was identified in many seabirds; mostly in immatures, but also in adults – during pre-breeding and post-breeding periods and among failed breeders. However, prospecting has not yet been documented among active breeders. We equipped 17 Common terns Sterna hirundo with GPS-UHF data-loggers and tracked their movements during late incubation and chick rearing in continental Croatia. We monitored the fate of their clutches until chicks left the nest. Birds of both sexes visited other breeding colonies within relatively short distances, while they still had active nests. These results confirm for the first time the presence of prospecting trips during incubation and chick-rearing in active breeders. Such behaviour probably developed because quick and unpredictable changes in their freshwater habitats can cause failure of whole colonies, forcing them to renest at other sites during the same breeding season. Prospecting during the first breeding attempt might shorten the renesting interval, and increase renesting success when multiple breeding sites are available on an easily accessible area. With increasing vulnerability of colony sites due to climate change, studies of scattered colonies are needed to better understand renesting and adult prospecting strategies.